PENGEMBANGAN BAHAN AJAR BERBASIS KOMIK DIGITAL PADA MATERI KEANEKARAGAMAN HAYATI DI DAERAHKU KELAS IV SD - Nur Wira Triana; Robenhart Tamba (JURNAL HANDAYANI PGSD FIP UNIMED, 2023)
Development of Digital Comic-Based Teaching Materials on Biodiversity Materials in My Area Grade IV Elementary School. The purpose of the research was to produce digital comic-based teaching materials on biodiversity materials in my area that are feasible, practical, and effective. This study used R&D with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model with the research subject of 30 students and grade IV teachers of SDN 105268 Telaga Sari. Data collection techniques use observation, tests, questionnaires, and documentation. The results of the study resulted in feasibility with an average percentage of 95% in the "Very Feasible" category, an average percentage of 94% in the "Very Practical" category. Furthermore, effectiveness through students' pretest and posttest scores with N-Gain 0.7 criteria is "Effective". So it is concluded that digital comic-based teaching materials can be used in the learning process.Keyword: Development, Teaching Materials, Digital Comics Pengembangan Bahan Ajar Berbasis Komik Digital pada Materi Keanekaragaman Hayati di Daerahku Kelas IV SD. Tujuan penelitian dilakukan untuk menghasilkan bahan ajar berbasis komik digital pada materi keanekaragaman hayati di daerahku yang layak, praktis, dan efektif. Penelitian ini menggunakan R&D dengan model ADDIE (Analysis, Design, Development, Implementation, and Evaluation) dengan subjek penelitian 30 siswa dan guru kelas IV SDN 105268 Telaga Sari. Teknik pengumpulan data menggunakan observasi, tes, angket, dan dokumentasi. Hasil penelitian menghasilkan kelayakan dengan persentase rata-rata 95% kategori “Sangat Layak”, uji praktikalitas persentase rata-rata 94% kategori “Sangat Praktis”. Selanjutnya, efektivitas melalui nilai pretest dan posttest siswa dengan N-Gain 0,7 kriteria “Efektif”. Sehingga disimpulkan bahan ajar berbasis komik digital dapat digunakan dalam proses pembelajaran..Kata Kunci: Pengembangan, Bahan Ajar, Komik Digital